Development of Meeting Management System for Faculty of Technical and Vocational Education - Siti Nur Azyan; Hamid, Hashima; Ahmad Rizal Madar (Research and Innovation in Technical and Vocational Education and Training, 2021)
Meeting management is an important aspect of planning, organizing, directing, coordinating and controlling activities. Today, meeting management has become a complex one that requires a systematic and efficient management system. Therefore, the development of this web-based Meeting Management System is intended to facilitate the management of meetings at the Faculty of Technical and Vocational Education as well as to refine the existing meeting management system, especially in terms of confirming attendance. The Meeting Management System includes aspects of faculty staff registration, department registration, new meeting registration and attendance confirmation. The system was developed by using Adobe Dreamweaver CS6 software for programming, MySQL for databases, and XAMPP as an internal browser. The development of this system uses the Waterfall model which is used as a guide in the development process so that it meets the characteristics and objectives set. Once the system was developed, it went through several tests by users and experts. This system is found to have several capabilities in helping to systematically organize faculty meetings. According to experts, the system is easy to use and easy to understand. Experts also think the presence verification function needs to be further enhanced to make this system a more complete system. The expected of the result Meeting Management System which can help to develop system for Faculty of Technical and Vocational Education of Universiti Tun Hussein Onn Malaysia can assist users, especially faculty and administration staff in managing meetings more efficiently.